Effects of 2.4 kg of proximal external loading on 5-km running performance - Sharp, D. W.; Swain, J. C.; Boy, T. G.; Killen, L. G.; Green, J. M.; O'Neal, E. K. (The Journal of Strength and Conditioning Research, 2022)
Racing weight is a popular topic in the running community. This study examined effects of modest loading via a ~2.4-kg soft and malleable weighted compression garment on overground running performance. Former and current collegiate cross-country runners (5 women and 6 men) completed 2 outdoor, solo road course runs 7 days apart on a familiar training route. During the first run (CON) subjects ran as closely as possible to their goal pace for a "hard speed day" workout based on predetermined paces according to current training level. During a subsequent run, subjects attempted to match their pace with aid from global positioning system watches and splits verbally announced on the course while wearing the weighted compression garment (LOAD). Metabolic data was later assessed during 5-minute running bouts on a treadmill with CON and LOAD conditions at subject's CON run pace. LOAD was slower (p < 0.01) at the 1.6-km mark (6:03 ± 0:37 vs. 6:13 ± 0:40) and finish (18:29 ± 2:06 vs. 19:15 ± 2:16). There was no differentiation (p > 0.05) between Vo2 (CON 3.47 ± 0.86; LOAD 3.56 ± 0.77 L·min-1) or respiratory exchange ratio (CON 1.05 ± 0.06; LOAD 1.06 ± 0.04) during the 5-minute running economy bouts. There was an inverse (r = -0.42) but nonsignificant (p = 0.22) relationship between percent difference in body mass and percent difference in performance. Metabolic variable differentiation was not detectable at race pace, but 2.4 kg of proximal loading resulted in an approximately 4% acute performance impairment.